A novel mutation in the HPGD gene causing primary hypertrophic osteoarthropathy with digital clubbing in a Pakistani family. (28th December 2017) - Khan, Anwar Kamal; Muhammad, Noor; Khan, Sher Alam; Ullah, Waheed; Nasir, Abdul; Afzal, Sibtain; Ramzan, Khushnooda; Basit, Sulman; Khan, Saadullah
Abstract: Primary hypertrophic osteoarthropathy (PHO) is a congenital multisystemic entity characterized by three major clinical symptoms: pachydermia, periostosis, and digital clubbing. Recently it has been reported that pathogenic mutations in two genes are known to be associated with PHO: HPGD and SLCO2A1 . In the present study, a five‐generation consanguineous Pakistani family harboring primary hypertrophic osteoarthropathy in autosomal‐recessive pattern was ascertained. Whole genome single nucleotide polymorphisms (SNPs) genotyping and sequence analysis revealed a novel homozygous missense mutation (c.577T˃C) of the human HPGD gene in all affected members of the family. The study presented here demonstrate the first case of primary hypertrophic osteoarthropathy reported in Pashtun population.